Metagenomic characterization of bacterial abundance and diversity in potato cyst nematode suppressive and conducive potato rhizosphere - John Kamathi Kiige; Agnes Mumo Kavoo; Mwashasha Rashid Mwajita; Derleen Mogire; Stephen Ogada; Tofick Barasa Wekesa; Leonard Muriithi Kiirika (PLoS ONE, 2025)
Potato (Solanum tuberosum L.) is an important food crop in Kenya, providing a source of nutrition and income for many farmers. However, potato cyst nematodes (PCN) cause significant damage to potato plants, leading to substantial economic losses and threatening the nation’s food security. Understanding the composition and functional potential of bacterial communities in the soil is important for developing sustainable biological control strategies against PCN and improving soil health. This cross-sectional purposive study examined the bacterial communities associated with PCN-suppressive and conducive potato rhizosphere from two major potato-producing counties in Kenya. We analyzed 180 soil samples from symptomatic and asymptomatic potato plants using shotgun metagenomics, followed by functional analysis to identify genes and metabolic pathways relevant to soil and plant health. Taxonomic classification revealed Enterobacteriaceae and Pseudomonadaceae as the most dominant bacterial families present. Within these families, the genera Pseudomonas and Enterobacter were highly abundant, both known for their plant growth-promoting traits, including biological control of soil pathogens and nutrient solubilization. KEGG and Pfam database analysis revealed pathways associated with nutrient cycling, transport systems, and metabolic functions. The abundance of iron-acquisition, chemotaxis, and diverse transport genes across analyzed samples suggests the presence of beneficial bacterial communities. This study provides the first report on bacterial ecology in PCN-infested rhizosphere in Kenya and its implications for soil health and PCN management.